KISAH DALAM AL-QUR’AN ; “NILAI-NILAI MORAL DAN PENDIDIKAN DALAM KISAH ASHABUL KAHFI: TELAAH TEMATIK AL-QUR’AN” - Suci Septiani; Achmad Abubakar; Halimah Basri (LPPM STAI Muhammadiyah Probolinggo, 2025)
One form of divine education for humans is realized through the stories told in the Koran. The story of Ashabul Kahf is part of the Qur'anic narrative which is full of values of faith, steadfast principles, and divine protection for a group of young people who maintain monotheism amidst the pressures of an infidel environment. This research aims to reveal the thematic meaning of the story of Ashabul Kahf through a maudhu'i (thematic) tafsir approach, by tracing the verses of the QS. Al-Kahf: 9–26 and examines various interpretations from classical and contemporary scholars such as Ibn Kathir, Al-Maraghi, and M. Quraish Shihab. This research uses a qualitative-descriptive method, with data collection techniques through literature studies that examine various relevant academic literature sources. The research results show that the story of Ashabul Kahf contains the main message about steadfastness of faith (tsabat al-iman), moral courage, and total surrender to Allah as a form of pure monotheism. This story also affirms God's power over time and human life, while also reflecting that God's protection and help will always accompany His faithful and consistent servants. The story's relevance in the contemporary context is evident in efforts to foster the character of the younger generation of Muslims, ensuring they remain steadfast in the values of faith and integrity amidst the challenges of modernity